Meta-analysis of the effect of probiotics or synbiotics on the risk factors in patients with coronary artery disease - Lei, Yunzhen; Xu, Min; Huang, Nanqu; Yuan, Zhengqiang (Frontiers in Cardiovascular Medicine, 2023)
Objective The objective of this study was to study the effect of probiotics or synbiotics on the risk factors for coronary artery disease (CAD) in the context of conventional drug therapy for CAD. Methods The literature on probiotics or synbiotics for the treatment of CAD was collected from PubMed, Scopus, Web of Science, Embase, and Cochrane Library. The search period was conducted on November 5, 2022, and the search covered all literature before November 5, 2022. The included literature consisted of randomized controlled trials of probiotics or synbiotics for CAD, and a meta-analysis was performed using Stata 14 software and RevMan 5.4 software. Results The meta-analysis explored the effect of probiotics or synbiotics on the risk factors for coronary artery lesions in a treatment setting with conventional medications for CAD. After a rigorous literature screening process, 10 studies were finally included for data consolidation to objectively evaluate the effect of probiotics or synbiotics on coronary lesions. The results of this study showed that the addition of probiotics or synbiotics to conventional medications for CAD reduced the levels of low-density lipoprotein cholesterol [weighted mean difference (WMD) −9.13 (−13.17, −5.09)], fasting glucose (FPG) [WMD −13.60 (−23.57, −3.62)], and hypersensitive C-reactive protein (hs-CRP) [standardized mean difference (SMD) −0.60 (−0.83, −0.37)] and increased the levels of high-density lipoprotein cholesterol (HDL-C) [WMD 1.94 (0.32, 3.57)], nitric oxide (NO) [WMD 5.38 (3.23, 7.54)] but did not affect the triglyceride (TG) level [WMD −13.41 (−28.03, 1.21)], systolic blood pressure (SBP) [WMD −0.88 (−3.72, 1.96)], or diastolic blood pressure (DBP) [WMD −0.21 (−2.19, 1.76)]. Conclusion Adding probiotics or synbiotics to conventional medications for CAD may improve patient prognosis. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022362711.